Improving of the Subgrade Soil using Chemical Additives - Khudhair, Abbas Ayad; Shaia, Hussein; Aodah, Haider Habeeb (Basrah Journal for Engineering Sciences, 2023)
Chemical additives were used in this research to improve the properties of the road subgrade layer. Cement, lime, and ferric chloride were used. Laboratory tests such as unconfined compressive strength, consistency limits, and wheel truck test were conducted. The results showed that adding these chemicals to the soil increases the ability of the soil to work, its resistance, and its durability. The optimum percentage of chemical additives that is suitable for the addition to the soil of Al-Nasiriya city were 9 %, 10 %, and 2 % corresponding to cement, lime, and ferric chloride, respectively. According to the unconfined compressive strength test and with increase curing period, which gave good results in improving the strength of the soil. As for the consistency limits, all additives reduced the liquid limit and plasticity index and increased the plastic limit, according to the wheel track test, at 10,000 passes the Rutting depth was 32 mm for natural soil, also the depths were (14, 19, and 17 mm) with chemical additives, respectively.